Clinical characteristics of actinic keratoses and their histological correlations: suggestion for a clinical severity scale - Arruda, Guilherme de Oliveira [UNESP]; Miola, Anna Carolina [UNESP]; Miot, Hélio Amante [UNESP]; Schmitt, Juliano Vilaverde [UNESP] (GN1 Sistemas e Publicacoes, 2022)
Introduction: Actinic keratoses are premalignant lesions with a risk of transformation to invasive squamous cell carcinoma. There is no identified correlation between clinical classification and histological grade of these lesions. Objectives: To correlate the clinical characteristics of actinic keratoses of the forearms and back of the hands with the degree of histological atypia (Keratinocyte Intraepidermal Neoplasia); to develop and validate a clinical severity scale correlated with the histological grade of actinic keratoses. Methods: Cross-sectional study with 162 actinic keratoses clinically evaluated for diameter, erythema, infiltration, hyperkeratosis, and exulceration and 34 lesions with different patterns were biopsied. Clinical features were correlated with the degree of histological atypia and p53 and Ki-67 expression. Results: Only the diameter of the lesions was significantly correlated with the degree of atypia (p=0.04), and only the erythema, hyperkeratosis, and the diameter linked with the immunohistochemical markings. A clinical score including diameter, hyperkeratosis, and exulceration was developed, which associated significantly with the degree of atypia (Spearman’s Rho=0.43; p=0.01). Conclusions: A score composed of diameter, hyperkeratosis, and exulceration correlated with the histological grade of actinic keratoses of the upper limbs was developed.
Características clínicas das queratoses actínicas e suas correlações histológicas: sugestão de escala de gravidade clínica
Keywords: Carcinoma in situ; Carcinoma squamous cell; Keratosis actinic; Skin diseases